Gender correlation between sleep duration and risk of coronary heart disease: a systematic review and meta-analysis - Li, Cun; Luo, Shun-xin; Liang, Tian-wei; Song, Dan; Fu, Jin-xiao (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe influence of extreme sleep duration on coronary heart disease (CHD) risk across genders remains a debated topic.MethodsThis analysis gathers observational studies that explore association between varying sleep durations and CHD risks. Trend estimation employs generalized least squares, converting specific category risk estimates into relative risks (RR) per hour of sleep increase. A two-stage hierarchical regression model evaluates potential linear dose-response relationships. Data analysis utilizes random-effects restricted cubic spline models with four knots.ResultsInvolving 17 studies and 906,908 participants, this meta-analysis identifies a pronounced U-shaped nonlinear relationship between sleep duration and CHD risk applicable to both genders (P < 0.01). Notably, shorter sleep durations are linked to higher CHD risks in women, whereas longer durations are more consequential for men. The optimal sleep duration for minimizing CHD risk is between 7.0–8.0 h daily for men and 7.5–8.5 h for women.ConclusionThe influence of sleep duration on CHD risk differs significantly between genders.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier (CRD42023478235).